METABOLITHOTROPIC ASPECTS OF CARDIOPROTECTIVE ACTION OF NEW COMBINED MEDICINE BASED ON L-ARGININE AND THIOTRIAZOLIN AT MODELING OF MYOCARDIAL INFARCTION - Ivanovna, Kucherenko Lyudmila; Fedorovich, Belenichev Igor; Antonovich, Mazur Ivan; Vladimirovna, Khromylova Olga (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objectives: The actual problem of modern medicine is the development of medications in treatment of cardiovascular system diseases. Different combinations of L-arginine with thiotriazolin in acute myocardial ischemia were examined as part of study and the optimal combination has been established - 4:1, named Argitryl.â€ The aim is to study the antioxidant, energotropic, and nitric oxide (NO)-modulating mechanisms of the cardioprotective effects of L-arginine with thiotriazolin (4:1) (Argitryl) drug candidate compared to 4.2% solution for injections Tivortinâ€ (TOV Yuriya-Farm,â€ Ukraine) on the model of pituitrin-isadrin infarction of myocardium in laboratory rats. Methods: The study was conducted in accordance with Guidelines of State Expert Center of the Ministry of Health of Ukraine. All manipulations were carried out in accordance with the European Convention for the protection of vertebrate animals used for experimental and other scientific purposes.â€ The experiments were performed on 40 white outbred rats weighing 170â€“180 g. The antioxidant activity of the drugs was assessed by reduction of biochemical marker oxidative stress and an increase in the activity of the antioxidant system of the myocardium. Results: The study of energy metabolism has shown that the modeling of myocardial infarction leads to typical ischemic injuries - decrease in ATP, discoordination of the Krebs cycle, activation of anaerobic glycolysis in the cytosolic fraction of the heart of rats from the control group. Administration of Tivortin to animals does not lead to a significant decrease in ischemic injuries in the energy metabolism of the myocardium. The brightest anti-ischemic effect was observed with the appointment of Argitryl.â€ Conclusion: The ascertained braking reaction of oxidative stress compared to the control group was found as a result of administration of Argitryl and Tivortin to animals with pituitrin-isadrin myocardial infarction. It was also found that the administration of Argitryl and Tivortin has a positive effect on the indices of the energy metabolism of the ischemic myocardium and leads to the normalization in conjugated NO system/renewed thiols. Argitryl significantly exceeds Tivortin on the influence of antioxidant, energy-tropic, and NO-modulating mechanisms of cardioprotective and anti-ischemic action on the studied indicators Â 